Contusion Spinе Injury in the Thoracolumbar Junction Region - Nekhlopochyn, O.S.; Verbov, V.V.; Tsymbaliuk, Ia. V.; Cheshuk, Ie. V.; Vorodi, M.V. (TERRA ORTHOPAEDICA, 2023)
Summary – Contusion spine injuries resulting from direct traumatic mechanisms that lead to spinal cord lesion are relatively rare during peacetime. The specific characteristics of such injuries are not extensively covered in contemporary literature. The need to optimize treatment methods for military personnel engaged in active combat operations on the territory of Ukraine necessitates an examination of this specific type of injury. Objective: To describe the clinical presentation and explore possible therapeutic approaches for closed contusion spinal cord injuries in the thoracolumbar junction. Materials and Methods: We conducted an analysis of patient data from those admitted for inpatient treatment at the Romodanov Neurosurgery Neurosurgery of National Academy of Medical Sciences of Ukraine, as well as patients referred to other healthcare institutions in Kyiv, from February 2022 to May 2023. Results: We analyzed the treatment outcomes of 5 patients, aged 27 to 53 years (mean age: 37.6 years), presenting with initial neurological deficits classified as ASIA A. Surgery was performed in 3 patients. All cases underwent wide laminectomy with facetectomy at the level of injury. Large arachnoid cysts were drained, and in one case, a subdural hematoma was removed. Posterior spinal fusion using an 8-screw transpedicular system was performed in all patients, utilizing a minimally invasive percutaneous approach. At the 2-month follow- up positive dynamics were observed in all patients. Neurological status improved to ASIA B in 2 cases and ASIA C in 1. Recovery of proprioceptive sensitivity was noted, as well as an increase in the intensity of neuropathic pain (up to 5-7 points at 2 months). In 2 patients undergoing conservative therapy, the neurological impairment level remained ASIA A, with pain intensity not exceeding 2 points. Conclusions: The findings emphasize the need for more comprehensive instrumental assessment in patients with suspected contusion spinal cord injuries. Active use of surgical treatment methods in this type of injury contributes to achieving better clinical outcomes.